2017
DOI: 10.1016/j.jmb.2017.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into Dimethylsulfoniopropionate Lyase DddY, a New Member of the Cupin Superfamily

Abstract: The marine osmolyte dimethylsulfoniopropionate (DMSP) is one of Earth's most abundant organosulfur molecules. Bacterial DMSP lyases cleave DMSP, producing acrylate and dimethyl sulfide (DMS), a climate-active gas with roles in global sulfur cycling and atmospheric chemistry. DddY is the only known periplasmic DMSP lyase and is present in β-, γ-, δ- and ε-proteobacteria. Unlike other known DMSP lyases, DddY has not been classified into a protein superfamily, and its structure and catalytic mechanism are unknown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
33
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 45 publications
3
33
1
Order By: Relevance
“…The K m value of DddK determined in this study is lower than that reported previously for the same strain (82 mM) (12), which may be caused by the different buffer systems used. The relatively high K m value, in the millimolar range, is common in many DMSP catabolic enzymes, including DMSP lyases DddP, DddQ, DddY, DddW, and Alma1 and the DMSP demethylase DmdA (11,20,(25)(26)(27)30). The intracellular concentration of DMSP in P. ubique HTCC1062 can reach 180 mM, while the concentration of DMSP in seawater is in the nanomolar level (12), indicating that an efficient transporter for DMSP is required.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The K m value of DddK determined in this study is lower than that reported previously for the same strain (82 mM) (12), which may be caused by the different buffer systems used. The relatively high K m value, in the millimolar range, is common in many DMSP catabolic enzymes, including DMSP lyases DddP, DddQ, DddY, DddW, and Alma1 and the DMSP demethylase DmdA (11,20,(25)(26)(27)30). The intracellular concentration of DMSP in P. ubique HTCC1062 can reach 180 mM, while the concentration of DMSP in seawater is in the nanomolar level (12), indicating that an efficient transporter for DMSP is required.…”
Section: Resultsmentioning
confidence: 99%
“…All the other known DMSP lyases generate acrylate and DMS from DMSP (15,18). The algal DMSP lyase Alma1 belongs to the aspartate racemase superfamily (11), DddP is a member of the M24 peptidase family (19), and the five remaining DMSP lyases (DddY, DddK, DddL, DddQ, and DddW) belong to the cupin superfamily and contain a conserved cupin motif (12,15,(20)(21)(22). Cupin superfamily proteins comprise functionally diverse enzymes, which contain a metal ion in their active sites (21,23).…”
mentioning
confidence: 99%
See 3 more Smart Citations